HAK-HAK TERSANGKA PADA TINGKAT PENYIDIKAN - Maknun, Luil (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
Law is a norm/rule that contains rules and provisions that guarantee individual and community rights and obligations. The existence of law is intended to create harmony in society, nation and state. How is the legal protection of the suspect's rights in the investigation of criminal cases. What is the potential for violations of law against the suspect's rights in the investigation of criminal cases. In this research using normative juridical method. Legal protection for the rights of suspects in the investigation of criminal cases, among others. Priority rights for settling cases, Right to preparation of defense, Right to give information freely, Right to get an interpreter, Right to get legal assistance and related to detention, Right to be notified, contact or receive visits from family, Right to present a de charge witness and expert witness. The role of law is needed in regulating the distribution of power and authority and its implementation among various state institutions and state apparatus so that the management of state life can be carried out in an orderly and orderly manner, and plays a role in vitalizing and functionalizing existing positive norms and values.